Simulasi Sistem Pelayanan Pemesanan Kedai Kopi XYZ Cabang Sidewalk - Jimbaran - Utami, Ni Made Cyntia; Sitanggang, Bryan Estavan Imanuel; Widhiatmika, I Wayan Ananta; Wahyuni, Ni Nengah Trisna; Aryani, Ni Ketut Indah (Engineering Faculty at Universitas Singaperbangsa Karawang, 2024)
Modeling real systems into a model is done through simulation, which is a method to replicate existing real systems with characteristics that are easier to observe than the original system. Kedai Kopi XYZ is one of the famous coffee brands in Indonesia. The location of the research carried out was at the XYZ Coffee Shop, Sidewalk branch, Jimbaran. The reason this place was used as a research location was because there were queues in the service system. The data that has been obtained from the field is then processed using Stat::Fit and ProModel. When the system with the existing data is run simulation, there are still blocks in the Entity States and there are full or bottlenecks in the Multiple Capacity Location States. Providing suggestions for improvements to minimize blocks and overflows in the system. The improvement proposed by observers is to improve capacity at locations in the system. By changing the existing capacity, minimal blocks and fulls will be produced and can be said to be reasonable in the system. Thus, it can be concluded that the model system at the XYZ Coffee Shop, Sidewalk branch, Jimbaran can work optimally.